2010
DOI: 10.1177/1088868309349693
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity as Identity: Toward an Understanding of Religion From a Social Identity Perspective

Abstract: As a social identity anchored in a system of guiding beliefs and symbols, religion ought to serve a uniquely powerful function in shaping psychological and social processes. Religious identification offers a distinctive "sacred" worldview and "eternal" group membership, unmatched by identification with other social groups. Thus, religiosity might be explained, at least partially, by the marked cognitive and emotional value that religious group membership provides. The uniqueness of a positive social group, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
569
1
28

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 624 publications
(614 citation statements)
references
References 91 publications
(147 reference statements)
16
569
1
28
Order By: Relevance
“…This reflects social identity theory, in that both types of activities were interactive group activities in which a sense of shared identity may be developed. Further, this finding supports the view of social identity theory that group membership provides emotional support to people in that group (Ysseldyk et al, 2010), especially for people who have an emotional attachment to that group (Liu, 2012). This is also supported by the qualitative findings in the present study, which indicated that in the SRT program participants provided emotional support to each other.…”
Section: Social Identity and Srtsupporting
confidence: 80%
See 3 more Smart Citations
“…This reflects social identity theory, in that both types of activities were interactive group activities in which a sense of shared identity may be developed. Further, this finding supports the view of social identity theory that group membership provides emotional support to people in that group (Ysseldyk et al, 2010), especially for people who have an emotional attachment to that group (Liu, 2012). This is also supported by the qualitative findings in the present study, which indicated that in the SRT program participants provided emotional support to each other.…”
Section: Social Identity and Srtsupporting
confidence: 80%
“…These similarities arose from food, former occupations and the places they came from. The sense of commonality among group participants could improve the sense of belonging (Song et al, 2014) and encourage the sense of shared social identity (Ysseldyk et al, 2010). This finding provides some support for the SRT program as a way of helping participants to develop shared identity and connectedness across perceived difference.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Much research has examined the different personality traits associated with religious group membership, though study of the same differences amongst non-religious individuals has been neglected. While there are a series of external factors which separate non-religious from religious individuals (Barber, 2011;Ysseldyk, Matheson, & Anisman, 2010) there may also be clear differences in individuals within this non-religious category.…”
Section: Introductionmentioning
confidence: 99%